Spectral Organization of the Human Lateral Superior Temporal Gyrus Revealed by Intracranial Recordings. (9th October 2012) - Nourski, Kirill V.; Steinschneider, Mitchell; Oya, Hiroyuki; Kawasaki, Hiroto; Jones, Robert D.; Howard, Matthew A.
Abstract : The place of the posterolateral superior temporal (PLST) gyrus within the hierarchical organization of the human auditory cortex is unknown. Understanding how PLST processes spectral information is imperative for its functional characterization. Pure-tone stimuli were presented to subjects undergoing invasive monitoring for refractory epilepsy. Recordings were made using high-density subdural grid electrodes. Pure tones elicited robust high gamma event-related band power responses along a portion of PLST adjacent to the transverse temporal sulcus (TTS). Responses were frequency selective, though typically broadly tuned. In several subjects, mirror-image response patterns around a low-frequency center were observed, but typically, more complex and distributed patterns were seen. Frequency selectivity was greatest early in the response. Classification analysis using a sparse logistic regression algorithm yielded above-chance accuracy in all subjects. Classifier performance typically peaked at 100–150 ms after stimulus onset, was comparable for the left and right hemisphere cases, and was stable across stimulus intensities. Results demonstrate that representations of spectral information within PLST are temporally dynamic and contain sufficient information for accurate discrimination of tone frequencies. PLST adjacent to the TTS appears to be an early stage in the hierarchy of cortical auditory processing. Pure-tone response patterns may aid auditory field identification.